Optimization Criteria for Entry into the Consolidated Group of Taxpayers in Order to Create an Effective Tax Mechanism and Improve the Social, Economic Development of Regions in the Russian Federation; Procedia - Social and Behavioral Sciences; Vol. 166 : Proceedings of The International Conference on Research Paradigms Transformation in Social Sciences 2014 (RPTSS-2014), 16–18 October 2014, Tomsk, Russia - Aktaev N. E. Nurken Erbolatovich; Bannova K. A. Kristina Alekseevna; Balandina A. S.; Dolgikh I. N. Irina Nikolaevna; Pokrovskaia N. V.; Rumina U. A.; Zhdanova A. B. Anna Borisovna; Akhmadeev K. N. (2015, 2015)
Title screen